Use of Acrylic Acid Sodium Acrylate Polymer to Maintain Cocoa Seed Viability (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2010)
The main problem of cocoa seed storage is moisture content of the seeds because cocoa seeds will germinate if cocoa seeds moisture content is high. The objective of this research is to maintain the cocoa seeds viability in storage using acrylic acid sodium acrylate polymer (AASAP). The function of AASAP is to absorb humidity in storage due to their ability to retain water and to prevent water loss. The experiment was conducted in a laboratory of Indonesian Coffee and Cocoa Research Institute and in Kaliwining Experimental Garden. This experiment was arranged by factorial randomized complete design, in wich AASAP dosages 0%; 0.1% (0.1 g/100 seeds); 0.2% (0.2 g/100 seeds), 0.3% (0.3 g/100 seeds), 0,4% (0,4g/100 seeds), combined with seeds storage period 1, 2, 3 and 4 weeks. The experiment used 3 replications and each repli cation used 100 seeds. Parameter of observation consisted of percentage of seeds germinated in storage, percentage of seeds infected by fungi in storage, seeds moisture content, percentage of seeds germination after storage, and early growth of cocoa seedlings. The results of the experiment showed that AASAP application with some dosages cocoa seeds storage cause to germinate in storage during 2 weeks. AASAP application with some dosages in cocoa seeds storage for 2 weeks would not result in infection by fungi and did not significantly affect seed germination after storage for 1, 2 and 4 weeks, and percentage of germination of cocoa seed after storage for 3 weeks decreased with increase dosage of AASAP. Higher dosage of AASAP would reduce early growth of cocoa seedling. Key words : Theobroma cacao, seed, acrylic acid sodium acrylate, seed storage, viabilty.